2014
DOI: 10.1016/j.ejvs.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed Foam Sclerotherapy of Great Saphenous Veins in Combination with Pre-treatment Reduction of the Diameter Employing the Principals of Perivenous Tumescent Local Anesthesia

Abstract: No benefit could be found using additional TA to reduce the vein diameter before the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…The rate of this kind of adverse event was in the range of thermal ablation of the GSV. 5 In the prior study of CA for varicose vein embolization, 8 21% of treated legs showed thrombus extension, suggesting a risk of inadvertent glue embolization to the pulmonary arteries. Even if it is clinically without meaning and spontaneous resolution occurred without specific treatment, these observations of extensions to the deep vein system might have been a matter of concern to some physicians.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The rate of this kind of adverse event was in the range of thermal ablation of the GSV. 5 In the prior study of CA for varicose vein embolization, 8 21% of treated legs showed thrombus extension, suggesting a risk of inadvertent glue embolization to the pulmonary arteries. Even if it is clinically without meaning and spontaneous resolution occurred without specific treatment, these observations of extensions to the deep vein system might have been a matter of concern to some physicians.…”
Section: Discussionmentioning
confidence: 97%
“…2 Whereas EVTA produces high venous occlusion rates with limited downtime, [3][4][5] it requires at least perivenous tumescent anesthesia, which can cause postoperative pain, bruising, and other complications, such as sensory nerve damage, 6,7 even if the last risk is difficult to differentiate from heat damage during endothermal treatment. Ultrasoundguided foam sclerotherapy is also widely used because of its low cost and high versatility, but success rates for treatment of the GSV are as low as 75%, 8 with frequently needed repetitive treatment sessions. Sclerotherapy is also marred by postprocedure inflammation and staining, visual disturbances, 20,21 and, rarely, stroke related to paradoxical air embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized clinical trial Devereux et al 46 recently showed no benefit from PST on LCFS. Nevertheless in this study unfortunately adrenaline or another spasm-inducing drug was not used in the tumescence solution, which may decrease the effectiveness of this complementary procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate manual compression on the SFJ during UGFS to minimize the flow of foam into the femoral vein171 . The use of tumescence anesthesia to improve results after UGFS shows no beneficial effect172 .…”
mentioning
confidence: 99%